Parametric study on buckling behaviour of castellated beam with sinusoidal openings - Bagal, Yashvardhan A.; Jamadar, Athar M.; Kumbhar, Popat D. (Journal of Structural Engineering, 2024)
Among the various failure behaviours of castellated beam (CSB), the buckling failure of web post is more critical because of increased web depth. The two prominent buckling failure modes of the castellated beam are Lateral Torsional Buckling (LTB) and Lateral Distortional Buckling (LDB) of web. Numerous studies regarding buckling behaviour of CSBs with commonly used hexagonal and circular openings have already been reported in the literature. In this paper, parametric study on CSBs with sinusoidal openings is carried out to investigate lateral torsional and distortional buckling of the web. Four CSBs are fabricated by varying the ratios of spacing between openings to opening depth (S/Do) and the overall depth to opening depth (D/Do) which are then experimentally tested under one-point loading. These CSBs are also analysed by using finite element-based ABAQUS software. After validating the numerical model of CSBs for load-carrying capacity and deflections with experimental results, the parametric study on 20 CSBs with varying S/Do and D/Do ratios is carried out to investigate the effect on failure load and failure modes. The investigation shows that a change in the S/Do ratio has negligible effect on failure load of LTB of CSBs whereas LDB failure load increases with an increase in the S/Do ratio. However, the failure load for LTB mode decreases with an increase in the D/Do ratio whereas failure load for LDB mode increases with an increase in the D/Do ratio. The study also shows that Finite element analysis can be satisfactorily used for the prediction of failure load and failure modes of CSBs.